2019
DOI: 10.1111/imr.12809
|View full text |Cite
|
Sign up to set email alerts
|

Exhaustion may not be in the human B cell vocabulary, at least not in malaria

Abstract: T cells exposed to persistent antigen in the inflammatory environment of chronic infections often show progressive loss of effector functions, high expression of inhibitory receptors and distinct transcriptional programs. T cells in this functional state are termed “exhausted” and T cell exhaustion is associated with inefficient control of infections. A remarkably similar scenario has been described for B cells during chronic infections in humans, including malaria, in which case a subpopulation of atypical me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…A scenario which mimics exhaustion in T lymphocytes, can affect B cells during chronic infection, inflammatory diseases ( 9 , 25 , 105 ) and cancer ( 106 ). B cell exhaustion manifests through the progressive loss of effector functions, of antibody and cytokine production, and high levels of inhibitory receptors.…”
Section: Discussionmentioning
confidence: 99%
“…A scenario which mimics exhaustion in T lymphocytes, can affect B cells during chronic infection, inflammatory diseases ( 9 , 25 , 105 ) and cancer ( 106 ). B cell exhaustion manifests through the progressive loss of effector functions, of antibody and cytokine production, and high levels of inhibitory receptors.…”
Section: Discussionmentioning
confidence: 99%
“…These cells express inhibitory receptors and have been described as functionally impaired (114,115), although several studies have reported that these cells may in fact be functional and can contribute to anti-parasite immunity (116,117). It has been postulated that naive B cells differentiate into atypical memory B cells in B cell follicles upon stimulation with interferon gamma produced by Th-1 polarized T follicular helper cells and Toll-like receptor agonists (118). In this process, atypical memory B cells may bypass the germinal center (GC) or exit the GC prematurely, thus limiting affinity maturation and the ability of these cells to produce high affinity antibodies.…”
Section: The Acquisition and Maintenance Of Humoral Immune Responses Against Plasmodium Falciparummentioning
confidence: 99%
“…In addition, these cells may accumulate during acute infection with SARS-CoV-2 infection (18,19). Although these B cells appear unresponsive to antigen stimulation through the B cell receptor (BCR) (7,20,21), it has been argued that they can be stimulated through antigen presented on membranes and differentiate into plasma cells (22).…”
Section: Introductionmentioning
confidence: 99%